Hospital capacities and shortages of healthcare resources among US hospitals during the coronavirus disease 2019 (COVID-19) pandemic, National Healthcare Safety Network (NHSN), March 27–July 14, 2020. (24th October 2022) - Wu, Hsiu; Soe, Minn M.; Konnor, Rebecca; Dantes, Raymund; Haass, Kathryn; Dudeck, Margaret A.; Gross, Cindy; Leaptrot, Denise; Sapiano, Mathew R. P.; Allen-Bridson, Katherine; Wattenmaker, Lauren; Peterson, Kelly; et al.
Abstract: During March 27–July 14, 2020, the Centers for Disease Control and Prevention's National Healthcare Safety Network extended its surveillance to hospital capacities responding to COVID-19 pandemic. The data showed wide variations across hospitals in case burden, bed occupancies, ventilator usage, and healthcare personnel and supply status. These data were used to inform emergency responses.